2020
DOI: 10.3389/fbioe.2020.00924
|View full text |Cite
|
Sign up to set email alerts
|

Safety Considerations in 3D Bioprinting Using Mesenchymal Stromal Cells

Abstract: Three-dimensional (3D) bioprinting has demonstrated great potential for the fabrication of biomimetic human tissues and complex graft materials. This technology utilizes bioinks composed of cellular elements placed within a biomaterial. Mesenchymal stromal cells (MSCs) are an attractive option for cell selection in 3D bioprinting. MSCs can be isolated from a variety of tissues, can pose vast proliferative capacity and can differentiate to multiple committed cell types. Despite their promising properties, the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 137 publications
(156 reference statements)
1
8
0
Order By: Relevance
“…As depicted in Figure , there was no observed difference in live/dead cells in co-cultures or MSC controls after day 35. This result indicated that the printing process does not significantly reduce the viability of the encapsulated cells compared to previously reported processes such as inkjet and laser printers . This is corroborated by Bian et al , where live/dead staining of human cells revealed that all MSCs and co-cultures (4:1) remained viable after 35 days in hyaluronic acid (HA) hydrogels.…”
Section: Discussionsupporting
confidence: 68%
“…As depicted in Figure , there was no observed difference in live/dead cells in co-cultures or MSC controls after day 35. This result indicated that the printing process does not significantly reduce the viability of the encapsulated cells compared to previously reported processes such as inkjet and laser printers . This is corroborated by Bian et al , where live/dead staining of human cells revealed that all MSCs and co-cultures (4:1) remained viable after 35 days in hyaluronic acid (HA) hydrogels.…”
Section: Discussionsupporting
confidence: 68%
“…Afterward, we evaluated the cell performance through indirect and direct contact cytotoxicity assays of bioink-based hydrogels. For this second set of assays, human bone-marrow-derived mesenchymal stromal cells (BM-MSCs) were chosen because of the increasing interest in this type of cells as biological building blocks for 3D bioprinting applications. , In the case of indirect assay, cytotoxicity and cell proliferation evaluation was performed in the presence of bioink-based hydrogel extracts (Figure c,d), showing no sign of cytotoxicity or detriment in proliferation. BM-MSCs were cultured using extracts isolated from the preincubation of bioink-based hydrogels in culture media.…”
Section: Resultsmentioning
confidence: 99%
“…The complexity and unpredictability of the 3D organ printing process, including issues such as biomaterial degradation, tissue integration, biocompatibility, and continuous tissue synthesis during material degradation, pose significant challenges. The potential for irreversible risks, such as cancer and dislodgement and migrations of the implant, is a further complication that defies easy resolution [ 12 , 13 , 16 , 18 , 21 , 22 ]. The impossibility of testing the safety of the organ before implantation, due to the organ being custom-made for the person in whom it will be implanted and therefore unable to be tested on others, is a further obstacle.…”
Section: Discussionmentioning
confidence: 99%